2017
DOI: 10.1016/j.neuron.2017.05.037
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 Depletion in Microglia Promotes Amyloid Clearance but Also Induces Synapse Loss

Abstract: SummaryMicroglia coordinate various functions in the central nervous system ranging from removing synaptic connections, to maintaining brain homeostasis by monitoring neuronal function, and clearing protein aggregates across the lifespan. Here we investigated whether increased microglial phagocytic activity that clears amyloid can also cause pathological synapse loss. We identified TDP-43, a DNA-RNA binding protein encoded by the Tardbp gene, as a strong regulator of microglial phagocytosis. Mice lacking TDP-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
154
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(169 citation statements)
references
References 70 publications
(83 reference statements)
15
154
0
Order By: Relevance
“…Under body injury stress, RACK1 will bind to and activate MTK1 and MAPKKK, leading to apoptosis. However, under hypoxic stress, the interaction between RACK1 and SGs will inhibit the activity of MTK1 and MAPKKK, thus inhibiting cellular apoptosis . This study confirmed that high expression of TDP‐43 can promote the formation of SGs.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Under body injury stress, RACK1 will bind to and activate MTK1 and MAPKKK, leading to apoptosis. However, under hypoxic stress, the interaction between RACK1 and SGs will inhibit the activity of MTK1 and MAPKKK, thus inhibiting cellular apoptosis . This study confirmed that high expression of TDP‐43 can promote the formation of SGs.…”
Section: Discussionsupporting
confidence: 68%
“…However, under hypoxic stress, the interaction between RACK1 and SGs will inhibit the activity of MTK1 and MAPKKK, thus inhibiting cellular apoptosis. 17 This study confirmed that high expression of TDP-43 can promote the formation of SGs. Therefore, we also measured the expression of MTK1 and MAPKKK phosphorylation in rat cartilage tissues.…”
Section: Figuresupporting
confidence: 72%
“…This represents the first in vivo demonstration of TDP-43 uptake by microglia as well as the prevention of TDP-43 spreading by normal microglia. Further study into the fate of TDP-43 and whether microglial function is altered following TDP-43 uptake in the zebrafish model may help expand upon the early evidence for microglial involvement in the progression of ALS/FTLD [8, 35, 46]. For example, phagocytosis of degradation-resistant TDP-43 aggregates [69] may disrupt the lysosomal pathway in microglia and, therefore, impair their ability for clearance of TDP-43.…”
Section: Discussionmentioning
confidence: 99%
“…For example, phagocytosis of degradation-resistant TDP-43 aggregates [69] may disrupt the lysosomal pathway in microglia and, therefore, impair their ability for clearance of TDP-43. Interestingly, Paolicelli et al have recently reported that TDP-43 depletion in Cx3Cr1-expressing cells (including microglia) led to an increase of phagocytosis and elevated transcription of lysosomal components [46]. This suggests that both endogenous and exogenously acquired TDP-43 may alter the functional behaviour of microglia, and contribute towards the progression of ALS/FTLD.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of microglia to strip or prune synaptic elements has been proposed to be both pathological (as in Alzheimer's Disease, Amyotrophic Lateral Sclerosis, and Lupus; Hong et al 2016;Shi et al 2017;Paolicelli et al 2017;Krasemann et al 2017;Bialas et al 2017) and neuroprotective (Chen et al 2014). At present it remains unclear whether the loss of perisomatic synapses following Toxoplasma gondii infection is pathological (and the direct cause of epileptiform activity) or beneficial (and may be a homeostatic response to other alterations following infection or inflammation).…”
Section: Loss Of Perisomatic Synapses Coincides With Microglial Enshementioning
confidence: 99%